BIOMIMETIC MINERALIZATION OF HYDROXYAPATITE ON A COLLAGEN-NANOFIBER COMPOSITE SCAFFOLD FOR BONE TISSUE ENGINEERING APPLICATIONS - Murat Arslan; Aylin Erdogan; Baran Akbulut (Journal of Biomedical and Techno Nanomaterials, 2025)
Bone tissue engineering seeks to develop biomaterial scaffolds that can replicate the complex hierarchical structure and biological functionality of native bone extracellular matrix. Conventional bone substitutes often fail to simultaneously achieve sufficient mechanical strength, osteoconductivity, and biological integration, limiting their effectiveness in repairing critical-sized bone defects. This study aims to develop a collagen–nanofiber composite scaffold functionalized through biomimetic mineralization of hydroxyapatite to enhance its suitability for bone tissue engineering applications. An experimental biomaterials approach was employed, involving fabrication of collagen nanofiber scaffolds followed by controlled biomimetic mineralization in simulated physiological conditions. The resulting scaffolds were characterized for morphology, mineral composition, crystallinity, and mechanical properties, and subsequently evaluated in vitro using osteogenic cell models to assess cell adhesion, proliferation, differentiation, and matrix mineralization. The mineralized scaffolds exhibited uniform nanoscale hydroxyapatite deposition, physiologically relevant Ca/P ratios, and significantly enhanced mechanical stiffness compared to non-mineralized controls. Biological assays demonstrated improved osteogenic cell attachment, elevated alkaline phosphatase activity, and increased calcium deposition on mineralized scaffolds. These findings indicate that biomimetic mineralization effectively integrates inorganic and organic phases to produce a scaffold that closely mimics native bone structure and function. In conclusion, collagen–nanofiber scaffolds mineralized with hydroxyapatite using a biomimetic approach represent a promising platform for bone tissue engineering and warrant further in vivo investigation.